Subcellular localised small molecule fluorescent probes to image mobile Zn2+. Issue 42 (15th October 2020) - Fang, Le; Watkinson, Michael
Abstract : A number of recently developed subcellular localised small molecule fluorescent probes to image mobile Zn 2+ are reviewed in this perspective. Abstract : Zn 2+, as the second most abundant d-block metal in the human body, plays an important role in a wide range of biological processes, and the dysfunction of its homeostasis is related to many diseases, including Type 2 diabetes, Alzheimer's disease and prostate and breast cancers. Small molecule fluorescent probes, as effective tools for real-time imaging, have been widely used to study Zn 2+ related processes. However, the failure to control their localisation in cells has limited their utility somewhat, as they are generally incapable of studying individual processes in a specific cellular location. This perspective presents an overview of the recent developments in specific organelle localised small molecule fluorescent Zn 2+ probes and their application in biological milieu, which could help to extend our understanding of the mechanisms that cells use to respond to dysfunction of zinc homeostasis and its roles in disease initiation and development.